1985
DOI: 10.1007/bf02541752
|View full text |Cite
|
Sign up to set email alerts
|

Thermal alteration of oleic acid in the presence of clay catalysts with co‐catalysts

Abstract: The effects of added co‐catalysts on the clay catalyzed polymerization of oleic acid have been investigated. Heating oleic acid at 230 C for 3 hr with a clay catalyst gave a polymer fraction (dimer and trimer acids, 35% yield) and a monomer fraction (branched chain isomers of oleic acid, 27% yield) as the major products. The variation in yield between the polymer and monomer products was found to be dependent upon the co‐catalyst used with the clay catalyst. For example, with both acidic and basic clays, polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…[45][46][47] As MoBUFA are interesting compounds as lubricants and for their use in cosmetics, 48 there exists a need for more selective processes. While some clays give moderate yields, [49][50][51][52] zeolites are used with more success [53][54][55][56][57][58] due to their relative small channels and pores. 47 As the zeolite pores are already blocked at the beginning of the reaction due to cokes formation, 47 the isomerisation takes place solely at the entrance of the micropores (Fig.…”
Section: Conversion Of Fats and Oilsmentioning
confidence: 99%
“…[45][46][47] As MoBUFA are interesting compounds as lubricants and for their use in cosmetics, 48 there exists a need for more selective processes. While some clays give moderate yields, [49][50][51][52] zeolites are used with more success [53][54][55][56][57][58] due to their relative small channels and pores. 47 As the zeolite pores are already blocked at the beginning of the reaction due to cokes formation, 47 the isomerisation takes place solely at the entrance of the micropores (Fig.…”
Section: Conversion Of Fats and Oilsmentioning
confidence: 99%
“…Several research groups have reported that UFA such as oleic acid (OA) can be converted to bc-isomers in the presence of clay catalysts such as bentonite and montmorillonite. In 1983, Foglia et al [1] reported that OA could be converted to a mixture of methyl bc-FA at up to 50% conversion when using a bentonite clay and dichloroethane as a co-catalyst [1,2]. In 1994, Neuss et al [3] reported that, with a montmorillonite clay catalyst in combination with an active carbon, sunflower oil FA/ esters could be converted to bc-isomers in yields between 30 and 40%.…”
Section: Introductionmentioning
confidence: 99%
“…Spiteller et al examined the positions of the methyl branches obtained from the monomeric fraction of the dimerization of pure oleic acid [18][19][20]. The formation of the methylbranched fatty acids can be rationalized by the protonation of the C,C double bond and following reactions of the adduct carbenium ions with other products of the dimerization, by transfer of a hydride ion [18] on the one hand or by cyclization and following ring opening of the three-membered ring carbocation intermediate on the other hand [21]. Isostearic acids with a branching at C2-C5 were not observed because carbenium ions with the positive charge in these positions cyclize to give the respective lactones [18].…”
Section: Heterogeneously Catalyzed Isomerization Reactionsmentioning
confidence: 99%